(untitled) (Research, Society and Development, 2018)
The purpose of this article is to present a study of school representations through drawings. In this work, we analyze the representations of the school space that some students did, through drawings. These representations were produced by male and female adolescents, who are between 15 and 18 years old and are in the 4th module of the Management course in Technical High School, in an institution of the private education network, located in the Metropolitan Region of São Paulo, Brazil. In the data collection process, students were asked to design the school as they saw it. Thus, the set of drawings provided us with rich material for analysis, which revealed that school is a significant place of relationships, source of experiences, learning and a space of contradictions.